1997
DOI: 10.1292/jvms.59.277
|View full text |Cite
|
Sign up to set email alerts
|

Selective Survival of a Thermostable Direct Hemolysin-Producing Vibrio parahaemolyticus in the Alimentary Tract of a Juvenile Estuarine Gastropod(Clithon retropictus).

Abstract: ABSTRACT. Juvenile estuarine gastropods (Clithon retropictus), maintained in ultraviolet ray-irradiated recirculating artificial seawater with a salinity of 20 at 28°C, preserved thermostable direct hemolysin (TDH)-producing strain D-3 of Vibrio parahaemolyticus at a level of 10 4 -10 5 colony forming units per gram (cfu/g) and TDH-non-producing strains N-18 and R-13 at a level of 10 1 -10 2 cfu/g in the alimentary tract for at least 21 days after ingestion. In adults, the numbers of the three strains decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
(21 reference statements)
0
11
1
Order By: Relevance
“…1), suggesting that TDH-producing strains would accumulate in estuaries where C. corona resides, through repeated passages of the strains in the gut of C. corona. In our previous studies, a TDH-producing strain, D3, was found to survive in the gut of a juvenile estuarine neritid gastropod, C. retropictus, at a level 100 times higher than TDH-non-producing strain R13 [7]. Based on this evi- dence, TDH-producing strains were suspected to accumulate in estuaries containing juvenile C. retropictus [7].…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…1), suggesting that TDH-producing strains would accumulate in estuaries where C. corona resides, through repeated passages of the strains in the gut of C. corona. In our previous studies, a TDH-producing strain, D3, was found to survive in the gut of a juvenile estuarine neritid gastropod, C. retropictus, at a level 100 times higher than TDH-non-producing strain R13 [7]. Based on this evi- dence, TDH-producing strains were suspected to accumulate in estuaries containing juvenile C. retropictus [7].…”
mentioning
confidence: 93%
“…The TDH-producing strains, D5 (O3:K6) and D12 (O3:K6), are nalidixic acid-resistant derivatives of clinical strains, while TDH-non-producing strains, R15 (O8:K41) and R13 (untypable), are rifampicin-resistant derivatives of environmental strains. The bacteria were grown overnight in Heart Infusion Broth (Eiken) supplemented with 3% NaCl at 37°C, washed with artificial seawater (ASW) [7] with a salinity of 35‰, and resuspended at 10 6 cfu/ml in ASW.The two neritid gastropods, C. corona and C. sowerbianus, were collected from Benoki and Ohura rivers in Okinawa, Japan. Adult and juvenile specimens, 9-13 mm and 5-7 mm in shell height, respectively, were cleansed of halophilic organisms of the gut by placement in recirculating freshwater at room temperature for one week.…”
mentioning
confidence: 99%
See 3 more Smart Citations